Centre Culturel Suisse Paris 2006 2007 2008. (Paris : Centre Culturel Suisse Paris, 2008)
Anüll, Ian ; Poloni, Marco ; Fischli & Weiss ; Dector et Dupuy ; Signer, Roman ; Renggli, David ; Gartentor, Heinrich ; Bischof, Werner ; Wekua, Andro ; Eloyan, Armen ; Chieppo, David ; Mosset, Olivier ; Loewensberg, Verena ; Decrauzat, Philippe ; Lohse, Richard Paul ; Gastaldon, Vidya ; Bove, Carol ; Comet, Al ; Trontin, Bernard ; Treichler, Franz ; Godoy, Marisa ; Perret, Mai-Thu ; Dias, Ligia ; Bachzetsis, Alexandra ; Bleuler, Tina ; Vanborm, Lies ; O'Neil, Amy ; Santos, Paula Dos ; Chaulvin, Célina ; Sofia-Paris, Cargo ; Mettler, Yves ; Perjovschi, Dan ; Humair, Daniel ; Auguste-Dormeuil, Renaud ; Lovay, Balthazar ; Wassmann, Lukas ; Aubry, Bastien ; Pilet, Guillaumet ; Trembley, Nicolas ; Blum, Dominik ; Pliakas, Marino ; Niggli, Lucas ; Garcia, Jacques ; Armleder, John ; Hostettler, Thomas ; Shahbazi, Shirana ; Andrade Tudela, Armando ; Elliman, Paul ; Bill, Max ; Marthaler, Christoph ; Bischoff, Duri ; Guyton, Wade
Engels
Frans
boek